O mądrym mężu, który wymyślił bogów. Mit antropogenetyczny w dramacie satyrowym „Syzyf” - Skarbek-Kazanecki, Jan (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2025)
The subject of this analysis is a fragment from the satyr play Sisyphus (T63 Laks, Most = 88 B25 DK = 43 F19 Snell). Although Sextus Empiricus (Adv. math. 9.54), to whom we owe the preservation of this fragment, attributed its authorship to Critias, a brutal Athenian politician from the 5th century BCE, a member of the oligarchic faction, also known as a poet. However, it is more likely that Sisyphus was written by Euripides. Thus, the text functions as a parody of sophistic discourse, voiced by the mythological trickster Sisyphus. The character’s monologue unfolds within a carefully structured narrative framework rooted in traditional anthropogonic myths. The tale of the “first human” rising above an animalistic existence (thēriṓdēs bíos, vv. 1–2) prompts reflections on the origins of religion, which is depicted as an instrument of manipulation: a fictional construct employed by powerful individuals to control the masses. This study situates the Sisyphus fragment within the broader intellectual context of late 5th-century BCE Athens, demonstrating how its narrative strategy allows the author to explore the boundaries of myth and its function in contemporary theatre.